Bottom-Up analysis of energy consumption and carbon emissions, with particular emphasis on human capital investment - Castesana, Paula (2013)
Short-term and mid-term projections of energy consumption and carbon emissions raise significant concern about the availability of the necessary energy resources to meet the growing demand and about the impact of emissions on global change. Different macroeconomic models address this issue through global variables, such as gross domestic product, production of goods and services, total population and natural resources extraction. However, the relations among these variables are neither linear nor simple. In an attempt to base said relations on a "bottom-up" perspective, the individual behavior of representative agents of economy, in terms of energy consumption and related carbon emissions, was stud-ied, with particular emphasis on their investment in human capital. It was found that a higher investment in human capital (e.g., education, research) was translated into a better distribution of consumption, with a higher level of energy efficiency and a slight improvement in carbon emissions intensity